Intergenerational Risk Sharing and Endogenous Labour Supply within Funded Pension Schemes. (28th April 2014) - Bonenkamp, Jan; Westerhout, Ed
<x xml:space="preserve">Abstract</x> Funded defined‐benefit pensions add to welfare on account of providing intergenerational risk sharing, but lower it on account of inducing labour supply distortions. We show that a properly designed funded defined‐benefit pension scheme involves a welfare improvement even if contributions are distortionary and even if individuals face potentially correlated wage and equity risks. Numerical calculations indicate that diversification gains from risk sharing are large compared to the losses related to labour supply distortions. This result withstands a number of extensions, like the introduction of a short‐sale constraint for individuals or the inclusion of a labour income tax.